A method for the generation of YAC transgenic mice by pronuclear microinjection. - Schedl, A (1993)
Yeast artificial chromosomes (YACs) represent the latest generation of vectors which have the great advantage of large insert size. The introduction of YACs into mammalian cells and organisms has become an important goal, since it offers the potential to study the control of large and complex transcription units and identify genes by complementation. Microinjection into the nucleus is the most direct and efficient way of delivering YAC DNA into cells, but requires the purification of the YAC from the remaining yeast chromosomes. Here we describe a detailed method for the isolation of pure, intact and highly concentrated YAC DNA. As a model system the murine tyrosinase gene was chosen and four YACs covering this locus were isolated. Introduction by homologous recombination in yeast of sequences permitting YAC amplification greatly facilitated the isolation of YAC DNA at high concentrations. YAC DNA stabilized in a salt and polyamine containing buffer did not compromise the survival of microinjected oocytes and was suitable for the generation of transgenic mice. Applications and benefits of this technique will be discussed.